Underwater forensic investigation - Becker, Ronald F. (CRC Press, 2013)
The evidence discovered at underwater crime scenes must be handled with the same attention to proper chain of custody procedures as with any other type of investigation. Improper handling of these scenes can lead to evidence being lost, unrecognizable, destroyed, contaminated, or rendered inadmissible at the time of trial. Updated and expanded, Underwater Forensic Investigation, Second Edition presents a comprehensive approach to the processing of an underwater crime scene and the steps necessary to conduct the operation. The book summarizes the history, physics, and laws applicable to underwa.